Analisis Kontekstual Wasiat Wajibah dalam Ayat Al-Qur'an dan Kompilasi Hukum Islam di Indonesia - Fatawi; Akhmad Dulfikar; Nurul Ma’rifah (Indonesian Journal of Humanities and Social Sciences, 2023)
In this research, Article 209 of the Compilation of Islamic Law (CIL) will be examined using the Quran. The question is whether the article is in accordance with the content of Surah Al-Baqarah, verse 180, which serves as the basis of mandatory inheritance. This conformity was examined through the contextual analysis proposed by Al-Balkhi. The terms "wâlidain" (parents) and "aqrabîn" (close relatives) are analyzed in the context of comparing them with other verses that encompass these two terms. The findings of this research can be stated as follows: Article 209 of the CIL has partially adopted the terms used in Surah Al-Baqarah, verse 180, where the beneficiaries of mandatory inheritance are stated as "lilwâlidain wal aqrabîn," meaning both parents and close relatives in the literal sense. However, Article 209 of the CIL has deviated from the context of the verse since it includes adopted children and adoptive parents who must still have a blood relationship with the adopting party. Additionally, Article 209 of the CIL only mentions adoptive fathers and children, and there are no provisions for adoptive siblings. Consequently, adoptive siblings’ rights are neglected because of the absence of such provisions in the CIL version.